Corpus-based research and pedagogy in EAP: From lexis to genre. (January 2015) - Flowerdew, Lynne
<x content-type="archive" xml:space="preserve">Abstract</x> This plenary paper showcases current corpus-based research on written academic English, illustrating the tight links that exist between corpus research and pedagogic applications. I first explicate Sinclair's concept of the 'lexical approach', which underpins much corpus research and pedagogy. I then discuss studies which focus on individual lexical items, phraseology (including lexical bundles) and rhetorical functions. Finally, I examine studies that combine Swalesian move structure analysis with corpus analysis. Throughout the paper, I highlight the importance attached to lexis in both corpus research and pedagogic applications of corpus findings in the realm of written discourse in English for Academic Purposes (EAP), covering both general and more specific purposes.